Bilateral pulmonary agenesis, oesophageal atresia, and the first arch syndrome. Issue 4 (July 1973) - DeBuse, P. J.; Morris, G.
Abstract : DeBuse, P. J., and Morris, G. (1973) . Thorax, 28, 526-528. Bilateral pulmonary agenesis, oesophageal atresia, and the first arch syndrome . This is the case report of an infant born alive with absence of both lungs, atresia of the oesophagus, and the first arch syndrome.